Kecerdikan Peulandok (Kancil) Dalam Cerita Rakyat Aceh: Refleksi Etika dan Strategi Sosial - Pratiwi, Fadila; Kussuji Indrastuti, Novi Siti (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
The folktale “Peulandok” discusses “cleverness” as a reflection of ethics and social strategy. Along with the development of the times, folktales are increasingly less popular among today's children. Its fading popularity among the current generation raises concerns about the loss of transmission of local wisdom values. This study aims to explain the story of “Peulandok” in the Acehnese narrative, ethics and positive social strategies that can be taken from the Peulandok story. The method used in this study is descriptive qualitative. Data collection techniques through interviews and reviewing the works of Acehnese artists related to the Peulandok story. Data analysis techniques through data reduction, data collection, data presentation, and drawing conclusions. The results of the study explain that the folktale about “Peulandok” or often called “Kancil” is a fairy tale made as a bedtime story for children. The narrative conveyed prioritizes “cleverness” in acting. The findings explain that the folktale “Peulandok” only aims to discuss the unique nature of “Peulandok” in deceiving its enemies. From the story of "Peulandok" can be used as a positive lesson related to the ethics of socializing with others, courage in acting, and being able to communicate well. In essence, this fairy tale has been passed down from generation to generation since ancient times until now. In addition, the discussion discussed is not to intimidate someone but is only humorous and unique story. Positive things that can be a narrative of how to adapt and socialize and maintain ethics in speaking well with others.